Foucault's Archaeology - Webb, David (Edinburgh University Press, 2021)
This book provides a new perspective on Foucault’s The Archaeology of Knowledge by revealing the extent to which its approach to language was influenced by the mathematical sciences. Setting out this background to Foucault’s analysis makes The Archaeology of Knowledge both accessible in a new way, and relevant to issues that are at the heart of much contemporary debate over the nature of critical thought and the relation between philosophy and the sciences. This book sheds new light on a crucial period of Foucault’s work by highlighting his relation to thinkers such as Cavaillès and Serres. It aims to provide a reading of The Archaeology of Knowledge that puts it at the heart Foucault’s thought. Rather than attempting a scientific study of language as such, Foucault is shown to have adopted a mode of thought indebted to thinkers in the scientific and epistemological tradition.